Audit Forensik, Audit Investigasi, dan Profesionalisme Terhadap Pengungkapan Kecurangan di BPKP - Cintya Nari Ratih, I Dewa Ayu; Sisdyani, Eka Ardhani (E-Jurnal Akuntansi; Vol 33 No 1 (2023)DO - 10.24843/EJA.2023.v33.i01.p11, 2023)
The research objective is to obtain empirical evidence of the effect of disclosing fraud on forensic auditing, investigative auditing and professionalism. The research was conducted at BPKP Bali Province. The number of samples used were 37 samples with purposive sampling method. The research instrument used was a questionnaire. The collected data were analyzed using multiple linear regression techniques. The results showed that the forensic audit had no effect on disclosing fraud, while the investigative audit and professionalism had a positive effect on disclosing fraud. The implications of this research are able to confirm the theory of fraud triangle and Theory of Planned Behavior (TPB) which argue that behavior does not only depend on a person's intentions, but also on other factors that are not under the control of the individual's behavior that causes fraud or fraud. Keywords: Forensic Audit; Investigative Audit; Professionalism; Fraud Disclosure